Functional analysis of F508del CFTR in native human colon - van Barneveld, Andrea; Stanke, Frauke; Tamm, Stephanie; Siebert, Benny; Brandes, Gudrun; Derichs, Nico; Ballmann, Manfred; Junge, Sibylle; Tümmler, Burkhard (Biochimica et biophysica acta, 2010)
The major cystic fibrosis mutation F508del has been classified by experiments in animal and cell culture models as a temperature-sensitive mutant defective in protein folding, processing and trafficking, but literature data on F508del CFTR maturation and function in human tissue are inconsistent. In the present study the molecular pathology of F508del CFTR was characterized in freshly excised rectal mucosa by bioelectric measurement of the basic defect and CFTR protein analysis by metabolic labelling or immunoblot. The majority of investigated F508del homozygous subjects expressed low amounts of complex-glycosylated mature F508del CFTR and low residual F508del CFTR-mediated chloride secretory activity in the rectal mucosa. The finding that some F508del CFTR escapes the ER quality control in vivo substantiates the hope that the defective processing and trafficking of F508del CFTR can be corrected by pharmacological agents. ► Freshly excised CF rectal biopsies showed mature F508del CFTR. ► High variability of F508del CFTR processing in CF patients´ intestine. ► No correlation between amounts of mature F508del CFTR and chloride secretion. ► Biosynthesis of band C F508del CFTR in wild-type amounts in CF tissues.